Peran Manajemen Risiko Dalam Meningkatkan Kualitas Pendidikan - Raisa Purnama Jingga; Irsyad, Irsyad; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study explores the role of risk management in improving school quality through a qualitative literature approach. Risk management in education serves as a structured process to identify, assess, and mitigate potential risks that may hinder the achievement of educational objectives. Schools are increasingly required to adopt proactive risk management strategies to address operational, financial, and reputational challenges. The study finds that effective risk management practices enhance institutional resilience, support continuous improvement, and foster a culture of accountability. By integrating risk management into school governance, educational institutions can improve decision-making, strengthen resource management, and ensure sustainable quality enhancement. This paper highlights the importance of risk management awareness among educators and policymakers in order to maintain the stability and integrity of educational organizations.